Isolation and characterization of antiplasmodial compounds from Siphonochilus aethiopicus and Aloe ferox and bioavailability of a novel furanoterpenoid - Lategan, Carmen (Division of Clinical Pharmacology, 2014)
Includes abstract. Includes bibliographical references (leaves 138-162).